2007
DOI: 10.1111/j.1360-0443.2007.01757.x
|View full text |Cite
|
Sign up to set email alerts
|

A case of late‐onset dependence on cocaine and crack

Abstract: Although dependence on cocaine among the elderly is considered very rare, clinical management can be challenging and is likely to require the involvement of several specialist and general health services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
1
2
0
Order By: Relevance
“…In 2014, an estimated 372 000 people in the United States over 50 had used cocaine or ‘crack’ in the past month, a number that increased to 562 000 in 2015 (SAMSHA ). These data are supported by case reports, with older cocaine users presenting in drug treatment (Kouimtsidis & Padhi ), emergency (Yarnell ) and urgent care (Yarnell ) settings. Presentation in generalist medical settings underlines the greater likelihood of adverse health implications of cocaine use in aging relative to younger users.…”
Section: Introductionsupporting
confidence: 62%
“…In 2014, an estimated 372 000 people in the United States over 50 had used cocaine or ‘crack’ in the past month, a number that increased to 562 000 in 2015 (SAMSHA ). These data are supported by case reports, with older cocaine users presenting in drug treatment (Kouimtsidis & Padhi ), emergency (Yarnell ) and urgent care (Yarnell ) settings. Presentation in generalist medical settings underlines the greater likelihood of adverse health implications of cocaine use in aging relative to younger users.…”
Section: Introductionsupporting
confidence: 62%
“…Some previous studies (Cumella & Kally, ,b; Krug et al, ) have also shown that these impulsive behaviours are more common among TAO patients than LAO eating disorder patients. Furthermore, psychoactive substance use disorders and impulsivity seem to decline substantially with age (Dom, D'Haene, Hulstijn, & Sabbe, ; Kouimtsidis & Padhi, ).…”
Section: Discussionmentioning
confidence: 99%
“…The demand on health and social care of people aged 65+ years needing support for problematic substance use is well documented [6,11,12]. For example, problematic use of alcohol and other drugs (AoD) including polypharmacy (over-the-counter and prescribed medication) is associated with increased use of emergency services and hospital admission [7,[13][14][15]. Older people with co-occurring conditions have been shown to experience delayed transfers after hospital admissions, premature transfer to long-term care and present more frequently with adult abuse [16][17][18].…”
Section: Problematic Substance Use In Later Lifementioning
confidence: 99%